Reproductive Health and Infectious Disease in the Middle East. - Barlow, Robin (Routledge Revivals Ser., 2018)
First published in 1998, this book covers a variety of health issues in the contemporary Middle east. Its thirteen chapters, contributed by a total of 23 authors and co-authors, reflect several different disciplines relevant for health studies, including epidemiology, economics and anthropology. In the field of reproductive health, there are chapters on maternal health indicators, fertility, infertility and the utilization of family planning services. In the field of infectious disease there are chapters on schistosomiasis, HIV/AIDS, hepatitis C, and Rift Valley Fever. Several different parts of the Middle East and North Africa are covered, including Tunisia, Egypt, Israel, Palestine and Lebanon. Problems of reproductive health and infectious disease in the region are seen to be more serious than generally recognised. There are significant cultural and political obstacles in both areas. A particular need is for greater empowerment of women as both clients and providers within the health care systems.